2015
DOI: 10.1039/c4dt02942a
|View full text |Cite
|
Sign up to set email alerts
|

Competitive formation of DNA linkage isomers by a trinuclear platinum complex and the influence of pre-association

Abstract: 2D [1H, 15N] HSQC NMR spectroscopy has been used to monitor the reaction of fully 15N-labelled [{trans-PtCl(NH3)2}2(μ-trans-Pt(NH3)2 {NH2(CH2)6NH2}2)]4+ (BBR3464 (15N-1)) with the 14-mer duplex (5’-{d(ATACATG(7)G(8)TACATA)}-3’. 5’-{d(TATG(18)TACCATG(25)TAT)}-3’ or I) at pH 5.4 and 298 K, to examine the possible formation of 1,4 and 1,5-GG adducts in both 5′ –5′ and 3′ –3′ directions. In a previous study, the binding of the dinuclear 1,1/t,t to I showed specific formation of the 5′ –5′ 1,4 G(8)G(18) cross-link,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…The initial orientation of BBR3464 on DNA mediated by electrostatic interactions transiently engaging with phosphate groups in the minor groove is an important feature which dictates not only isomer directionality but also the final conformation of covalently-bound interstrand crosslinks (1,4 versus 1,6) because in some cases the covalent adduct can be formed directly but in others, diffusion off the DNA is necessary for covalent binding to occur. These subtleties can be followed by 2D { 1 H, 15 N} HSQC NMR 30,31…”
Section: Primary Techniquesmentioning
confidence: 99%
“…The initial orientation of BBR3464 on DNA mediated by electrostatic interactions transiently engaging with phosphate groups in the minor groove is an important feature which dictates not only isomer directionality but also the final conformation of covalently-bound interstrand crosslinks (1,4 versus 1,6) because in some cases the covalent adduct can be formed directly but in others, diffusion off the DNA is necessary for covalent binding to occur. These subtleties can be followed by 2D { 1 H, 15 N} HSQC NMR 30,31…”
Section: Primary Techniquesmentioning
confidence: 99%
“…The energy of interaction showed that the interaction SI-PPC···1HPN is thermodynamically favorable, expressing negative mean of Gibbs’ free energy values along the simulated trajectory. Upon initial molecular recognition, the next step in the reaction will be monofunctional binding of one Pt unit to the biomolecule, as seen for the binding of triplatin to DNA. , The molecular dynamics (MD) simulations of compounds I - 3 , II-3x , and II-3y were therefore performed, where these are monofunctional carboxylate bound adducts of triplatin with the two disaccharides. For II , both 1 C 4 ( x ) and 2 S 0 ( y ) ring conformations for the IdoA­(2S) residue were modeled, noting that for the 1:1 triplatinNC/FPX adduct, the conformational ratio of the 1 C 4 / 2 S 0 forms of the FPX residue IdoA­(2S) is altered from ca.…”
Section: Resultsmentioning
confidence: 99%
“…The results were consistent with those found for 15 N-BBR3464. 6,20 Upon addition of the dodecamers a downfield shift of 0.07-0.13 ppm for both peaks is observed in the proton dimension at pH 7, Table 1. The fact that the protons of the Pt-15 NH 3 as well as the Pt-15 NH 2 CH 2units are affected to the same extent indicates that both groups are equally involved in the binding process.…”
Section: Dickerson-drew Dodecamermentioning
confidence: 98%